(untitled) (Fiep Bulletin - online, 2020)
Introduction: The significant increase in the number of work-related musculoskeletal disorders has left entrepreneurs and labor institutions in a state of concern. The growing phenomenon of the D.O.R.T is becoming increasingly prominent in the news and on remoteness. Objective: The present study aimed to evaluate the implementation of Labor Massage in the Sala Estado do Bem Estar, in the Business Group in São Paulo, through the Labor Massage Program by the Nessi Institute of Massage Therapy, a program that has been widely used as a method of WMSD prevention Methodology: A total of 234 employees were evaluated over a three-month period: 145 female employees (62.00%) and 89 male employees (38.00%). The Labor Massage Program was coordinated and applied by the staff of the Nessi Institute of Massage Therapy five times a week for 15 minutes daily. Results: Through this research that deploying the State Welfare Room, within a Business Graphic Group, to promote Labor Massage to employees, favored a 72% reduction in muscle pain, had an 80% improvement in domestic and professional activities without limitations, After the three months of evaluation and care, only 14% were in medical consultation, and only 13% were still in pain. Conclusion: The Labor Massage, can promote many benefits for the welfare and quality of life for employees.